Sunflower - Ponti, Carlo; Cohn, Arthur; de Sica, Vittorio; Guerra, Antonio; Zavattini, Cesare; Mdivani, Gheorgij; Loren, Sophia; Mastroianni, Marcello ([Rome] C. C. Champion S.p.A., 1970)
Giovanna (Loren) and Antonio (Mastroianni) are a newly-wed couple who are separated at the outbreak of World War II when Antonio goes to Russia with the Italian army. When he does not return at the end of the war, Giovanna goes to Russia to look for him and finds that he has a new life there.
VHS
An Italo-French co-production, C.C. Champion S.p.A., Rome [and] Les Films Concordia, Paris.
Sophia Loren, Marcello Mastroianni.
Keywords: Drama